(3eGgjI GdfbhO hNUGFUgG, GdeDSSGJ GdfbOjI, GdfbhO hGdeJZjQGJ GdEbJUGOjI s - (3CSGeI(B, (3cGeds ((3GdEScfOQjI(B:s (3ecJHI GdhaGA GdbGfhfjI(B,s, 2017)
(3JfGhd GdcGJH aj gPG GdeDda GdfbhO hGdCfXeI GdfbOjI GdCNQi, GVGaI Gdi OQGSGJ GdeDSSGJ GdfbOjI hGdeGdjI eQhQG HGdYedjI GdGFJeGfjI hCShGb GdGFJeGf GVGaI Gdi GdHfc GdJLGQjI ef MjK YedjGJgG hhVGFagG hOhQgG GdMjhj, Ke GdHfhc GdeQcRjI hOhQgG GdgGe GdQbGHI Ydi GdHfhc GdJLGQjI, Ke fJfGhd GdeDSSGJ GdfbOjI hGdeGdjI GdhSjWI hGdHhQUGJ ef MjK CgejJgG hJfXjegG Ke eTcdI dSjQ dg hJCKjQgG Ydi GdfbhO Ke GdfXQjGJ GdfbOjI GdeNJdaI hCNjQG fJfGhd eTcdI GdJVNe hCSHGHgG hBKGQgG(B.s
Keywords: (3GdHfhcs; (3GdeDSSGJ GdeGdjIs; (3GdeDSSGJ GdfbOjIs; (3GdeJZjQGJ GdGbJUGOjIs; (3GdfbhOs